1033. RHODODENDRON STARLINGII: Ericaceae. (26th August 2022) - Rushforth, Keith; Huong, Nguyen Thi Thanh; Yamanaka, Masumi
Summary: Rhododendron starlingii Rushforth & Nguyen Thi Thanh Huong, from Fan Si Pan, Vietnam's highest mountain, is described as a new species and illustrated. It is related to R. crenulatum from Pu Bia, Laos' highest mountain, but differs in several characters.